Poznańskie dzbanki miodowe z Rochlitz - Kowalczyk, Andrzej (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The paper presents two fragments of beer mugs discovered during archaeological excavations in Poznań at number 21/22 Szyperska Street (ul. Szyperska), which are often referred to as honey jugs from Rochlitz. They are characterised by zones covered with fluting and brown and yellow glazing. The context of the discovery suggests that the vessels, manufactured in the first half of the 18th century in Saxony, either in Rochlitz or Lunzenau, might have belonged to a merchant living in Poznań in a Jewish district.
Honey jugs from Rochlitz found in Poznań